In need of review: Developing Sensory Provision in Northern Ireland's Mainstream Primary classrooms. Issue 3 (2nd June 2021) - Beck, Gillian J.; O'Connor‐Bones, Una; Gracey, Jackie; Kelly, Greg; Walsh, Glenda
Abstract : The impact of Sensory Processing Difficulties across a range of Special Educational Needs is well researched. More recently, the impact on children's mental health and well‐being, linked with anxiety, depression and self‐injurious behaviours, have redirected international research to consider the holistic benefits of sensory provision, for those with special educational provision and the wider classroom population. A SMART SURVEY was designed to collate empirical evidence regarding current sensory awareness and provision in mainstream primary schools throughout Northern Ireland, in a time efficient manner. Out of 809 schools, 164 (20.27%) fully completed the online survey. Findings indicate that Special Educational Needs Coordinator confidence in developing practice, supporting staff and children was limited and impaired by insufficient and inconsistent training opportunities. While healthcare research recommends provision by trained professionals, Occupational Therapy input was limited (n = 34; 24.8%), resulting in practice that could be detrimental rather than beneficial to children's progress. Respondents identified a need for sensory training for teachers (n = 124; 93.94%) to ensure that the impact of Sensory Processing Difficulties on the holistic development of all children is understood. Pupil voice was undervalued (n = 5; 3.6%). Active involvement of children in the process of evaluation and intervention is recommended to enhance pupil autonomy and well‐being.